2020
DOI: 10.1177/1687814020910537
|View full text |Cite
|
Sign up to set email alerts
|

Complementary ensemble adaptive sparsest narrow-band decomposition method and its applications to the gear crack fault diagnosis

Abstract: Adaptive sparsest narrow-band decomposition is the most sparse solution to search for signals in the over-complete dictionary library containing intrinsic mode functions, which transform the signal decomposition into an optimization problem, but the calculation accuracy must be improved in the case of strong noise interference. Therefore, in combination with the algorithm of the complementary ensemble empirical mode decomposition, a new method of the complementary ensemble adaptive sparsest narrow-band decompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Wang [15] used EMD and Teager Kaiser energy operator technology to process the signal and identify the crack fault according to the time-domain and side-frequency characteristics of the processed signal. Peng et al [16] combined with EMD technology, proposed the complementary ensemble adaptive sparsest narrow-band decomposition to diagnose the fault according to the side frequency distribution characteristics of the cracked gear signal. Wang et al [17] found the optimal demodulation subband based on genetic algorithm and then carried out envelope analysis to identify the gear crack fault through the side frequency characteristics of the fault signal.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [15] used EMD and Teager Kaiser energy operator technology to process the signal and identify the crack fault according to the time-domain and side-frequency characteristics of the processed signal. Peng et al [16] combined with EMD technology, proposed the complementary ensemble adaptive sparsest narrow-band decomposition to diagnose the fault according to the side frequency distribution characteristics of the cracked gear signal. Wang et al [17] found the optimal demodulation subband based on genetic algorithm and then carried out envelope analysis to identify the gear crack fault through the side frequency characteristics of the fault signal.…”
Section: Introductionmentioning
confidence: 99%